Microbiological Quality Status Of Dried Squid (Loligo Sp.) Marketed In Pasar Pagi Arengka Market Of Pekanbaru - Rika Sepia Alvianti; Bustari Hasan; Dian Iriani (Berkala Perikanan Terubuk, 2023)
This study aims to evaluate the microbiological quality status of dried salted squid marketed in Pasar Pagi Arengka Market of Pekanbaru. Dried salted squid from different regional origin and storage times were sampled from the market. The samples were taken randomly from three traders and analized for moisture, microbiological and sensory quality. The moisture, microbiological and sensory quality of the dried salted squid varies between product origins and storage time. The dried salted squid from Tanjung Pinang and Sibolga contains moisture 28,02% and 29,21%, Aw 0,71 and 0,72 , salt 14,35% and 13,57%, ALT 2,9 x 104 and  3,3 x 104 CFU/gram, total Halophilic 1,9 x 104 and 2,2 x 104 CFU/gram, Coliform 17 and 6,1 MPN/g, total Staphylococcus aureus 2,4 x 102 and 5,6 x 102 CFU/gram, Listeria monocytogenes negative. Overall, moisture, salt, ALT, total Halophilic, total Staphylococcus aureus, Listeria monocytogenes of the products were within the value recommended by SNI. In order to minimize the health risks to consumers, it is recommended that dried salted squid be consumed with minimal delay and cooked properly before consumption.